2006
DOI: 10.1007/s10803-006-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Maladaptive Behavior in Children with Smith-Magenis Syndrome

Abstract: Children with Smith-Magenis Syndrome (SMS) exhibit deficits in adaptive behavior but systematic studies using objective measures are lacking. This descriptive study assessed adaptive functioning in 19 children with SMS using the Vineland Adaptive Behavior Scales (VABS). Maladaptive behavior was examined through parent questionnaires and the Childhood Autism Rating Scale. Cognitive functioning was evaluated with an age-appropriate test. Children scored below average on VABS Communication, Daily Living Skills, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 32 publications
8
50
1
5
Order By: Relevance
“…An earlier study concluded that children with SMS have difficulty regulating activity level, affect, and bodily functions and that sleep disturbance represented the most significant factor predicting these challenging behaviors (Dykens & Smith, 1998). Additional scientific publications have reported the presence of peculiar movements, stereotypical behaviors, hyperactivity, and sensory-processing difficulties in children with SMS (Dykens, Finucane, & Gayley, 1997;Dykens & Smith, 1998;Finucane, Konar, Haas-Givler, Kurtz, & Scott, 1994;Gropman et al, 2006;Hicks, Ferguson, Bernier, & Lemay, 2008;Martin et al, 2006). Sensory integration disorders have also been included as neurobehavioral problems common to SMS (Gropman et al, 2007;Smith & Gropman, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study concluded that children with SMS have difficulty regulating activity level, affect, and bodily functions and that sleep disturbance represented the most significant factor predicting these challenging behaviors (Dykens & Smith, 1998). Additional scientific publications have reported the presence of peculiar movements, stereotypical behaviors, hyperactivity, and sensory-processing difficulties in children with SMS (Dykens, Finucane, & Gayley, 1997;Dykens & Smith, 1998;Finucane, Konar, Haas-Givler, Kurtz, & Scott, 1994;Gropman et al, 2006;Hicks, Ferguson, Bernier, & Lemay, 2008;Martin et al, 2006). Sensory integration disorders have also been included as neurobehavioral problems common to SMS (Gropman et al, 2007;Smith & Gropman, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to severe sleep disturbances characterized by decreased total nighttime sleep, increased nighttime arousals, and daytime sleepiness occurs and has been associated with an unusual inverted circadian melatonin rhythm Gropman, Elsea, Duncan, & Smith, 2007). Early expressive speech delays with and without hearing loss and mild to severe cognitive deficits are observed (Greenberg et al, 1996;Madduri et al, 2006;Martin, Wolters, & Smith, 2006;Udwin & Webber, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides hyperactivity and attention seeking, patients with SMS may present agressive and self-injurious behavior, including hand biting, head banging, face slapping, self-hanging, onychotilomania and polyembolokotonia [16,19,[29][30][31][32][33][34][35]. Other signs reported in up to 50% of patients include obesity, cardiacs defects, seizures, cleft lip/palate and male hypogonadism [22].…”
Section: Childhood/adolescencementioning
confidence: 99%
“…In comparison to other groups, SMS is associated with relatively high levels of aggression, as well as a range of stereotypical behaviors (Dykens, Finucane, & Gayley, 1997;. Estimates of the prevalence of SIB in SMS vary between 67-96% Finucane, Dirrigl, & Simon, 2001;Greenberg et al, 1996;Martin, Wolters, & Smith, 2006). Some topographies of SIB, such as onychotillomania (pulling out finger-and toenails) and polyembolokomania (insertion of objects into body orifices) appear to be relatively unique to the syndrome (e.g., Finucane, Dirrigl, & Simon, 2001).…”
mentioning
confidence: 99%